2012
DOI: 10.1007/978-3-642-29320-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Towards Model-Based Testing of Electronic Funds Transfer Systems

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We stumbled upon this problem in our attempt to apply input-output conformance testing (ioco) [7,8] to an industrial embedded system from the banking domain [1]. A schematic view of the implementation under test (IUT) and its environment is given in Figure 1.(a).…”
Section: Introductionmentioning
confidence: 99%
“…We stumbled upon this problem in our attempt to apply input-output conformance testing (ioco) [7,8] to an industrial embedded system from the banking domain [1]. A schematic view of the implementation under test (IUT) and its environment is given in Figure 1.(a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is interesting to find out which composition of programming constructs and / or patterns of interaction satisfy the constraints established in this paper. The research reported in this paper is inspired by our practical experience with testing asynchronous systems reported in [1]. We plan to apply the insights obtained from this theoretical study to our practical cases and find out to what extent the constraints of this paper apply to the implementation of our case studies.…”
Section: Discussionmentioning
confidence: 99%
“…We stumbled upon this problem in our attempt to apply input-output conformance testing (ioco) [9,10] to an industrial embedded system from the banking domain [1]. A schematic view of the implementation under test (IUT) and its environment is given in Figure 1.(a).…”
Section: Introductionmentioning
confidence: 99%
“…A schematic view of a typical MBT ecosystem is given in Figure 1. The figure refers to the ecosystem used in our earlier experience with model-based testing of an embedded system in the financial domain [3]. The MBT process starts with making test models from the requirements and standards.…”
Section: Model-based Testingmentioning
confidence: 99%